اثر تقلبات سعر الصرف على ميزان المدفوعات دراسة قياسية لحالة الجزائر من 1990-2020 - حمدي صهيبة; رحماني امينة; عامر ابراهيم (جامعة عمار ثليجي الاغواط, 2022)
This study aims to measure the impact of exchange rate fluctuations on the Algerian balance of payments in the period from 1990 to 2020, by identifying various theoretical aspects of the exchange mechanism and the components of the balance of payments, in addition to addressing the actual relationship between them based on econometric modeling through the use of bound test for cointegration and error correction model. The findings showed the existence of an integration relationship between the balance of payments and the exchange rate, but this relationship was weak with regard to the exchange rate, as we concluded that the exchange rate was ineffective in achieving balance in the balance of payments.